Early-life group size influences response inhibition, but not the learning of it, in Japanese quails - Willcox, Kathryn; Vernouillet, Alizée; Lens, Luc; Verbruggen, Frederick (Learning & behavior, 2025)
In complex social environments, animals benefit from suppressing inappropriate responses (known as Response Inhibition) to avoid conflicts and maintain group cohesion. Recent research suggests that an individual's early-life social environment can shape their response inhibition. However, these findings have mostly been correlational, and results vary across species. Furthermore, the role of learning is often overlooked when measuring response inhibition, despite its potential importance to understanding group differences. We investigated the effect of early-life group size, a key determinant of social complexity, on response inhibition in Japanese quails ( Coturnix japonica ), whilst taking the role of learning into account. Quails (n = 120) were raised in either small groups of five or large groups of 15 individuals. Response inhibition was assessed using the cylinder task. Up to ten trials were administered to assess whether the birds’ responses changed with increasing experience of the task. Among the quails that completed ten trials, we found that those raised in large groups consistently spent less time pecking the cylinder than those raised in small groups. The quails’ responses were also influenced by their body condition, food motivation and sex. Importantly, the quails learned to inhibit their responses – successful trials increased, and time spent pecking the cylinder decreased, across ten trials. However, learning rates did not differ between the treatment groups. These findings suggest that early-life social group size promotes the development of response inhibition in quails, but not their learning of it, during the cylinder task.